PENGARUH MENAJEMEN LABA PADA RETURN SAHAM DENGAN KUALITAS AUDIT DAN CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI - Indrayanti, Ni Putu Ayu Desy; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2017)
The effort in maximizing the return is the main purpose of a company. This is because a high return reflects the company's ability to generate profits. The purpose of this study was to determine the effect of earning management in stock returns with the quality of the audit and corporate governance as moderating variables.The study was conducted on all companies listed in Indonesia Stock Exchange 2011-2015 with a total population of 2422 companies. Samples were obtained by 28 companies with a total of 80 observations using non-probability sampling with purposive sampling technique. Moderated regression method was used in analyzing the data.The analysis found that earning management has no effect on stock returns. The audit quality able to moderate the effect of earning management in stock returns. Corporate governance is not able to moderate the effect of earning management in stock returns.
Keywords: earning management, audit quality, corporate governance and stock returns